The A Research Article on Antistress Activity of Herbal Extract Oil of Piper Methysticum on Wistar Albino - Sharma, Ankit; Mukim, Mohammad; Ancheria, Rahul; Jangid, Hrishab (Asian Journal of Pharmaceutical Research and Development, 2021)
The research was carried out to determine the antistress activity of piper methysticum and the animal model used was wistar albino due to it’s worldwide acceptability in researches related to psychology .kava (piper methysticum) root extract was used for abundance of kavlactones hence for the sake of study different percentage of suspensions like 4%, 6%, 8%, 12%, 18%, 30% were prepared and diazepam was selected as standard drug.oecd guideline 423 was followed during acute toxicity studies.no symptoms of acute toxicity was seen during 14 days observational period when given a dose of 2000 mg/kg so on this basis two dose level of 200mg/kg and 400 kg were selected for antistress activity.test model selected for antistress activity were forced swim test, tail suspension test and anoxia stress tolerance test.for respective tests a sharp decline in duration of immobility and increase in anoxia stress tolerance was seen.hence we can conclude that piper methysticum can play a significant role in the field of treating stress after futhur extensive clinical research.